2018
DOI: 10.1016/s0140-6736(18)31363-1
|View full text |Cite|
|
Sign up to set email alerts
|

Baricitinib for systemic lupus erythematosus: a double-blind, randomised, placebo-controlled, phase 2 trial

Abstract: Eli Lilly and Company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
263
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(305 citation statements)
references
References 26 publications
5
263
1
16
Order By: Relevance
“…In a pre-clinical study, tofacitinib (a JAK1and JAK3 inhibitor) reduced both kidney disease and the concentration of pathogenic autoantibodies in lupus-prone mice 87 . The results of a phase II trial of baricitinib 88 (an oral JAK1 and JAK2 inhibitor) in 314 patients with SLE who have active cutaneous disease or musculoskeletal activity were reported in 2018. 67% of patients receiving 4mg/day baricitinib achieved a SLEDAI-2K response at 24 weeks, which was significantly more than those receiving placebo (53%; P=0.04) 88 .…”
Section: [H2] Targeting the Interferon Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In a pre-clinical study, tofacitinib (a JAK1and JAK3 inhibitor) reduced both kidney disease and the concentration of pathogenic autoantibodies in lupus-prone mice 87 . The results of a phase II trial of baricitinib 88 (an oral JAK1 and JAK2 inhibitor) in 314 patients with SLE who have active cutaneous disease or musculoskeletal activity were reported in 2018. 67% of patients receiving 4mg/day baricitinib achieved a SLEDAI-2K response at 24 weeks, which was significantly more than those receiving placebo (53%; P=0.04) 88 .…”
Section: [H2] Targeting the Interferon Pathwaymentioning
confidence: 99%
“…The results of a phase II trial of baricitinib 88 (an oral JAK1 and JAK2 inhibitor) in 314 patients with SLE who have active cutaneous disease or musculoskeletal activity were reported in 2018. 67% of patients receiving 4mg/day baricitinib achieved a SLEDAI-2K response at 24 weeks, which was significantly more than those receiving placebo (53%; P=0.04) 88 . Treatment with 4mg/day baricitinib also reduced the proportion of patients with 'worst joint pain' compared with placebo and improved PGA and low disease activity scores; however, the 2mg/day dose of baricitinib did not show any benefit compared with placebo 64 .…”
Section: [H2] Targeting the Interferon Pathwaymentioning
confidence: 99%
“…Amidst this backdrop exist signs of hope. Phase II study results of baricitinib, an oral selective and reversible JAK1 and JAK2 inhibitor (4), and ustekinumab, an anti-IL-12/23 mAb (5), have been promising. Post hoc analysis from a phase II study (6) of the anti-IL-6 mAB PF-04236921 revealed efficacy and safety, and trends toward treatment response were observed in a recent phase IIb trial (7) and long-term extension study (8) of atacicept, a dual inhibitor of a proliferation-inducing ligand (APRIL), and B cell activating factor of the TNF family (BAFF).…”
mentioning
confidence: 99%
“…Установлена быстрая положительная динамика артрита (n=4) и кожной сыпи (n=6), в отсутствие нормализации титров анти-ДНК и С3-компонента комплемента. Совсем недавно были получены данные РПКИ (фаза II; n=314; 24 нед) о применении барицитиниба при СКВ с преимущественным поражением суставов и кожи [118]. Пациенты были рандомизированы на три группы: барицитиниб 4 и 2 мг/сут и ПЛ -и получали стандартную базовую терапию, включающую нестероидные противовоспалительные препараты, ГК в дозе ≤20 мг/сут, ГХ или один иммуносупрессивный препарат (МТ, азатиоприн или микофенолата мофетил).…”
unclassified